If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying g(g + 5) = 0 Reorder the terms: g(5 + g) = 0 (5 * g + g * g) = 0 (5g + g2) = 0 Solving 5g + g2 = 0 Solving for variable 'g'. Factor out the Greatest Common Factor (GCF), 'g'. g(5 + g) = 0Subproblem 1
Set the factor 'g' equal to zero and attempt to solve: Simplifying g = 0 Solving g = 0 Move all terms containing g to the left, all other terms to the right. Simplifying g = 0Subproblem 2
Set the factor '(5 + g)' equal to zero and attempt to solve: Simplifying 5 + g = 0 Solving 5 + g = 0 Move all terms containing g to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + g = 0 + -5 Combine like terms: 5 + -5 = 0 0 + g = 0 + -5 g = 0 + -5 Combine like terms: 0 + -5 = -5 g = -5 Simplifying g = -5Solution
g = {0, -5}
| 5-9x=30-4x | | -9k+k=-4 | | 6x+6=6x | | 16x^2/3/2x | | -6-3=3-6x | | 5(x-6)+9=-13 | | 12x-8y=10 | | 5A-c=3a+2 | | 3p/4-17=-11 | | -3(x+6)-44=8-55 | | 25x+7-28x=1-9 | | -5x+16.9=4.4 | | 6(x-2)=4x-(2x+7) | | 5x-4=14x-44 | | -1.2+w/8=-26.8 | | 5(y-5)=10 | | 4x+31=13x-1 | | 52-11+2n=59 | | 15=6b+4b-1-6B | | 3x=18.75 | | 14x+17y=52 | | v/15.36=6 | | 6x-2y=-11 | | 22.4=7w | | 5y-30x=-19 | | 5=y/1.25 | | 4x-12y=60 | | 4y/9=8 | | 6y-3+5y=9y-4 | | 3/4y=24 | | M-3/2=5 | | 6x^2-10=16 |